Genetic predisposition of cholesterol gallstone disease - Alejandro Hernández-Nazará; Fátima Curiel-López; Erika Martínez-López; Zamira Hernández-Nazará; Arturo Panduro (Annals of Hepatology, 2006)
Gallstone disease (GSD) is the result of the interaction between genetic and environmental factors and it is a major disease cause of surgery with high costs to health systems. Worldwide prevalence varies according to the ethnic population suggesting that high prevalence of GSD in certain ethnic groups is due to the presence of genetic factors implicated in different metabolic pathways. However, environmental factors play a determinant role in gene expression. This review summarizes the genes involved in biliary salt and cholesterol synthesis, lipids transport and the Lith genes. Future studies should be focused on the study of interactions between genetic and environmental factors which could be specific for each population.